Cumplimiento de la obligatoriedad contable en la Piladora “OLGUITA” - López Guerrero, Manuel Eduardo (2017)
This case study is entitled "COMPLIANCE OF THE ACCOUNTING OBLIGATORY IN THE PILADORA" OLGUITA ", a company located in the city and canton Babahoyo, and is considered a subject of great importance, relevance and interference in the economic development of this sector of the Ecuadorian homeland. The present case study is based on research and analysis through the analytical method and has the purpose of determining the causes that cause the non-compliance of accounting obligation in the company object of study rice paddy "Olguita", for it will apply techniques of collection of data as an interview which will determine the administrative activities performed by the manager whether or not they contribute significantly to the development of the company. The piladoras of rice as in the case of Piladora "Olguita", are companies that execute different processes among which are: Process of reception, Process of pilado, Process of storage and sale. It is necessary to determine in each of these processes the costs incurred both in raw material and in the provision of service to farmers in the area. Accounting is a necessity that has any natural or legal person who carry out commercial, industrial or service activities, which will allow real, accurate and timely information on the resources of the Olguita